Benign multicystic mesothelioma arising from the tunica vaginalis. Issue 1 (24th January 2019) - Lang, Andrew; Chaudhri, Preeti
Abstract: Benign multicystic mesothelioma is an extremely rare neoplasm usually arising from the visceral mesothelium of the peritoneal cavity typically presenting in young to middle-aged women. It has been deemed an indolent tumour with a possible heritable nature, but also a possible reactive neoplasm secondary to trauma. Diagnosis relies on identifying characteristic histology of cysts separated by loose connective tissue stroma and lined by pale, flat or cuboidal mesothelial cells. A 74-year-old male presented with a painless, enlarging scrotal swelling thought to be either an epididymal cyst or hydrocele. He underwent radical orchiectomy and benign multicystic mesothelioma of the tunica vaginalis was characterized on macroscopy and microscopic examination. The potential for malignant transformation of these tumours has not been demonstrated, but they are known to recur. This infrequent presentation of a rare and poorly understood tumour with description of histologic findings may allow for improved diagnosis in other cases.